Gambaran Bentuk dan Ukuran Styloid Process Serta Bentuk Kepala Kondilus Ditinjau Dari Radiografi Panoramik di RSGM “X” - Wa Ode Sitti Muthmainah; Hendra Polii; Anie Apriani; Dian Lesmana (SONDE (Sound of Dentistry), 2024)
Panoramic radiography is the most frequently used diagnostic tool by dentists. In addition to the teeth and supporting tissues, other surrounding structures must also be interpreted, one of which is the styloid process and condyle. In some cases, elongation of the styloid process and calcification of the stylohyoid ligament can cause symptoms called Eagle syndrome, in this condition it also affects the head of the condyle so that it often experiences temporomandibular joint disorders. This information is important to be able to detect abnormalities that occur early so that appropriate treatment can be carried out. The purpose of this study was to determine the general description of the morphology of the condyle head and the average length of the styloid process. The method used in this study is descriptive observational with a cross-sectional research design. Samples consist of 116 panoramic radiography of 58 male subjects and 58 female subject. All data were collected from Maranatha Dental Hospital. Study shows that the shape of the most condylar heads was convex and there was no significant difference in the length of the styloid process in male and female. This study concludes that the shape of the condyle head in subjects is convex, and the average length of the styloid process (right and left sides) is 21.80 mm (21.78 and 21.82) mm.